Hubungan Pengetahuan dan Sikap Ibu Tentang Gizi dengan Kejadian Anemia Pada Ibu Hamil di Puskesmas Umbulharjo 1 Yogyakarta: The Relationship Between Maternal Knowwledge and Attitudes About Nutrition and the Incidence of Anemia in Pregnant Women in Puskesmas Umbulharjo 1 Yogyakarta - Stefania Widyanti Serang; Chentia Misse Issabella; Indah Purnamasari (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
The Relationship between Maternal Knowledge and Attitude about Nutrition with the Incidence of Anemia in Pregnant Women at Puskesmas Umbulharjo 1 Anemia is a condition where the number and size of red blood cells, or hemoglobin concentration is below a specified limit value, resulting in damage to the blood's capacity to transport oxygen throughout the body. According to the World Health Organization (WHO), in 2018, 40% of maternal deaths in developing countries were related to anemia in pregnancy. To determine the relationship between maternal knowledge and attitudes about nutrition and the incidence of anemia in pregnant women at Umbulharjo Community Health Center 1. Non-experimental quantitative research method with a cross-sectional design using primary data from interviews or questionnaires and secondary data from Umbulharjo Community Health Center I and Yogayakarta city health department. Of the 39 respondents, it was found that the majority of mothers who had good knowledge had a good attitude, namely (82.1%). Based on the chi square test results, the p-value was 0.000, which means there is a relationship between maternal knowledge and attitudes about nutrition and the incidence of anemia in pregnant women in the Umbulharjo Community Health Center area 1. There is a relationship between maternal knowledge and attitudes about nutrition and the incidence of anemia in pregnant women at Umbulharjo Community Health Center area 1.